Representation of Masculinity in the Character Kiriko in the Film The Boy and the Heron (Roland Barthes' Semiotic Analysis) - Sugara, Rangga; Mustika, Sri; Corliana, Tellys (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study examines the representation of masculinity within the female body through the character Kiriko in The Boy and the Heron (2023), directed by Hayao Miyazaki. Using Jo Ann Arinder’s feminist theory, the research highlights how Kiriko embodies masculine traits such as physical strength, courage, and leadership that are traditionally associated with men in gender constructions. Through a qualitative approach and narrative analysis of visuals and dialogue, the study reveals that Kiriko serves as a symbol of resistance against the stereotype of passive and weak women. She appears as a nurturing figure who also protects and leads, thereby blurring the boundaries between masculinity and femininity. These findings affirm that gender representation in animation can be fluid, creating space for new interpretations of female identity in popular media. The study also illustrates how Studio Ghibli consistently presents complex and strong female characters, while promoting values oriented toward social change in its visual storytelling.